2012
DOI: 10.1088/1748-6041/7/3/035010
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and skeletal myotube formation capability of C2C12 and H9c2 cells on isotropic and anisotropic electrospun nanofibrous PHB scaffolds

Abstract: This study aims at investigating the behavior in terms of the proliferation and skeletal muscle differentiation capability of two myoblastic cell lines, C2C12 and H9c2, on both isotropic and anisotropic electrospun nanofibrous poly(hydroxybutyrate) (PHB) scaffolds, as well as on PHB films and polystyrene controls. After a careful characterization of the matrices in terms of surface morphology, surface roughness and mechanical properties, the proliferation rate and the capability of the two cell lines to form s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 45 publications
4
68
0
Order By: Relevance
“…The design of a tissue-specific scaffold, however, faces numerous challenges related to material choice and processing. Indeed, the influence of mechanical, chemical and architectural properties of the substrate material on the morphology, proliferation and differentiation of myoblasts has been clearly demonstrated (Engler et al 2004, Riboldi et al 2005, Choi et al 2008, Guex et al 2012, Ricotti et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of a tissue-specific scaffold, however, faces numerous challenges related to material choice and processing. Indeed, the influence of mechanical, chemical and architectural properties of the substrate material on the morphology, proliferation and differentiation of myoblasts has been clearly demonstrated (Engler et al 2004, Riboldi et al 2005, Choi et al 2008, Guex et al 2012, Ricotti et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Myoblasts and myotubes aligned on substrates with groove widths of 0.45-50 μm, with a minimal threshold requirement of 130 nm. An alternative strategy consists of electrospinning synthetic polymers to produce parallel-oriented nano-or micron-scaled fibres (Riboldi et al 2005, Choi et al 2008, Aviss et al 2010, Ricotti et al 2012. Additionally, we have recently shown (Guex et al 2012) that myoblasts align preferentially on parallel-oriented nano-to submicron-sized fibres of poly(ε-caprolactone) (PCL), as compared to those randomly oriented.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on PHB based esophagus implants suggested that PHAs can promote muscular regeneration and that they can be applied as esophagus substitutes (Mack et al 2008;Gredes et al 2009;Ricotti et al 2012). Some of the studies using P(3HB-co-3HHX) as artificial esophagus showed that it can stimulate regeneration of the removed esophagus of dogs.…”
Section: Pha Implants: Esophagusmentioning
confidence: 99%
“…It has recently been shown, that myoblastic cell lines, such as mouse myoblasts C2C12 and embryonic rat myocardium cells H9c2, can proliferate and differentiate on nanofibrous poly(3)hydroxybutyrate (PHB) scaffolds, as well as PHB films (Ricotti et al, 2011(Ricotti et al, , 2012. The reaction of the skeletal muscle tissue to intramuscular insertion of polymeric PHB implants was expressed in a transient post-traumatic inflammation and the formation of a fibrous capsule.…”
Section: Tissue Response-histological Examinationsmentioning
confidence: 99%